REGIONAL TOURISM BRAND – NEED OR NECESSITY IN THE ASPECT OF SOCIO-ECONOMIC DEVELOPMENT OF POLISH MOUNTAIN RURAL AREAS - Hyski, Marcin; Chudy-Hyski, Dorota (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper discusses the issue of the regional tourism brand, which is a significant differentiator of the area in the market and gives the opportunity to include tourism in the model of socio-economic development of the region. The analysis of regional branded tourist products includes mountain rural areas of Poland. These areas are an example of a region with unfavourable farming conditions, which makes the competitive position of these areas in a much worse position than other rural areas in the country. Due to the difficulties in the sphere of social and economic life occurring in mountain rural areas, they require other alternative development incentives. Tourism can be one of these, but to make the development through tourism effective, attention must be focused on building a strong regional brand, which is the competitive strength of the area. Mountain rural areas have their own specific potential, which allows them to build regional branded tourist products easily distinctive from lowland rural areas. The aim of the paper is to indicate the importance of the region's tourism brand on the example of mountain rural areas of Poland, including its constituent elements. The paper uses a descriptive and qualitative analysis method that allowed to identify problems of mountain rural areas development and the role of tourism and in particular the tourism brand in the development of such areas. The analysis includes literature in the field of economic sciences, including economies of regions, economies of tourism, and territorial marketing. The paper covers the issues of development of mountain rural areas with an indication of their main socio-economic development problems. Then, against the background of the concept of the region in economic terms, mountain rural areas have been presented as a tourist region where tourism can be an important factor of development. The text also covers selected issues related to the creation of a regional tourism brand, and characterizes the regional tourism brand of mountain rural areas, together with their constituent elements.